2007
DOI: 10.4049/jimmunol.179.10.6514
|View full text |Cite
|
Sign up to set email alerts
|

CD4+CD28null T Cells in Autoimmune Disease: Pathogenic Features and Decreased Susceptibility to Immunoregulation

Abstract: To determine the role of expanded CD4+CD28null T cells in multiple sclerosis and rheumatoid arthritis pathology, these cells were phenotypically characterized and their Ag reactivity was studied. FACS analysis confirmed that CD4+CD28null T cells are terminally differentiated effector memory cells. In addition, they express phenotypic markers that indicate their capacity to infiltrate into tissues and cause tissue damage. Whereas no reactivity to the candidate autoantigens myelin basic protein and collagen type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
102
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 169 publications
(112 citation statements)
references
References 47 publications
9
102
1
Order By: Relevance
“…However, the reason for their expansion remains elusive. Studies regarding the antigen-specificity of CD4 þ CD28 À T cells have indicated that the majority of CD4 þ CD28 À T cells are CMV-reactive [64,65], and that at least part of this population proliferates in response to autoantigens [3,9,48]. In line with these reports, we found that the MS-related autoantigens MBP and MOG elicited degranulation of CD4 þ CD28 À T cells in a donor dependent manner.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…However, the reason for their expansion remains elusive. Studies regarding the antigen-specificity of CD4 þ CD28 À T cells have indicated that the majority of CD4 þ CD28 À T cells are CMV-reactive [64,65], and that at least part of this population proliferates in response to autoantigens [3,9,48]. In line with these reports, we found that the MS-related autoantigens MBP and MOG elicited degranulation of CD4 þ CD28 À T cells in a donor dependent manner.…”
Section: Discussionsupporting
confidence: 86%
“…In line with these reports, we found that the MS-related autoantigens MBP and MOG elicited degranulation of CD4 þ CD28 À T cells in a donor dependent manner. In addition, our previous study demonstrated that most CD4 þ CD28 À T cells of HC, MS and RA patients proliferated in response to CMV [48]. Researchers recently demonstrated that CMV-reactive CD4 þ T cells acquire distinct functional properties reminiscent of antiviral CD8 þ T cells [66].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Aging of the immune system, also called immunosenescence, has been found to be accelerated in patients with a diverse range of autoimmune diseases. 25,26 Given the relatively low odds ratio (1:18) 8 of the IL-7Ra gene regarding its association to MS, a small effect on the MS risk could be expected. However, the results described here clearly show a significant effect of Hap4 on the frequency of RTEs.…”
Section: Functional Analysis Of Il-7ra Haplotypes B Broux Et Almentioning
confidence: 99%